Lidocaine inhibits glioma cell proliferation, migration and invasion by modulating the circEZH2/miR-181b-5p pathway. Issue 1 (6th January 2021) - Wen, Jian; Li, Xin; Ding, Yan; Zheng, Shaohua; Xiao, Ying
Abstract : Background: Lidocaine is well known as a local anesthetic that has been reported to play an antitumor role in numerous cancers, including glioma. Circular RNAs (circRNAs) play multiple biological roles in cancers. The aim of this study was to determine the effects of lidocaine in glioma in vitro and in vivo and explore functional mechanisms. Methods: The effects of lidocaine on glioma progression were investigated by cell proliferation, migration and invasion using 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay, colony formation assay and transwell assay. The expression of CD133 and glial fibrillary acidic protein (GFAP) was quantified by western blot to assess cell differentiation. The expression of circEZH2 and miR-181b-5p was detected by a quantitative real-time PCR (qRT-PCR). The target relationship between circEZH2 and miR-181b-5p was verified by dual-luciferase reporter assay and RNA immunoprecipitation (RIP) assay. The effect of lidocaine on tumor growth in vivo was investigated by establishing Xenograft models. Results: Lidocaine inhibited proliferation, migration, invasion and induced differentiation of glioma cells in vitro . Lidocaine suppressed the expression of circEZH2, and circEZH2 was highly expressed in glioma tissues and cells. CircEZH2 overexpression partly inhibited the function of lidocaine. CircEZH2 was a sponge of miR-181b-5p, and miR-181b-5p was downregulated in glioma tissues and cells. Besides, miR-181b-5p restoration reversed the effects of circEZH2 overexpression to repress the malignant behaviors of glioma cells. In addition, lidocaine mediated the circEZH2/miR-181b-5p axis to inhibit tumor growth in vivo . Conclusion: Lidocaine suppressed glioma progression by modulating the circEZH2/miR-181b-5p pathway.